Seismic response of nuclear power station with disconnected pile-raft foundation using dynamic centrifuge tests. (15th December 2022) - Yang, Yang; Fan, Hong; Cheng, Yi Pik; Gong, Weiming; Dai, Guoliang; Liang, Fayun; Jia, Yajie
Abstract: The typical foundation type for a nuclear power station is the raft foundation in rock areas. With the power demand, it is possible that a nuclear power station located in soft soil areas. Traditional connected pile raft foundation (CPRF) has been successfully used in soft soil areas. However, under earthquake loads, high horizontal shear stresses and bending moments are generated in the pile head. Accordingly, researchers have sought to develop an innovative disconnected pile raft foundation (DPRF), and the benefits of DPRF have simulated increasing researches on it in the last two decades. In this study, a series of dynamic centrifuge tests were carried out to identify the effect of cushion and its thickness on the dynamic characteristics of the nuclear power station with DPRF. A withe noise excitation and three earthquake waves with different seismic intensities were adopted as ground motion. The seismic responses of soil, structure, and bending moment of piles were analysed. A cushion thickness equal to the diameter of piles is recommended. Comparing with the CPRF, the cushion layer of DPRF has an isolation benefit. With the gravel cushion, attention must be paid to the horizontal displacement, inclination and rocking of the superstructure. Graphical abstract: Image 1